MATHEMATICAL PROBLEM-SOLVING ABILITY OF STUDENTS IN TERMS OF ADVERSITY QUOTIENT AND SELF-EFFICACY - Suci Charolina; Suhendra Suhendra (Jurnal Eduscience)
Purpose – This study aims to analyze students' mathematical problem-solvingproblem-solving skills in SPLDV material in terms of adversity quotient and self-efficacy and provide recommendations for improving students' mathematical problem-solvingproblem-solving skills in schools with comparable backgrounds.